A comparison of natalizumab’s effects on SDMT between pediatric-onset and adult-onset multiple sclerosis patients - Puthenparampil, Marco; Scialpi, Graziana; Gaggiola, Marta; Zanotelli, Giovanni; Miscioscia, Alessandro; Berardi, Angela; Riccardi, Alice; Nosadini, Margherita; Sartori, Stefano; Perini, Paola; Rinaldi, Francesca; Gallo, Paolo (Frontiers in Neurology, 2024)
Background. A wide range of cognitive deficits has been described also in Pediatric-Onset Multiple Sclerosis (POMS) patients. Thus, the therapeutic approach should be designed on both preventing cognitive worsening and enhancing cognitive improvement. Aim. We explored the effect of natalizumab (NTZ) on Symbol Digit Modality Test (SDMT) in both POMS and Adult-Onset MS (AOMS). Method. Sixty-three patients (34 AOMS and 29 POMS) were enrolled in this retrospective, single-centre study. Patients were clinically and radiologically followed up every six months. They also perform SDMT at baseline and after at least 24 months. SDMT values were reported as corrected values (cSDMT) and z-scores (zSDMT). Annualized cSDMT and zSDMT was calculated dividing the difference between scores by follow-up (expressed in years). Results.Although annualized cSDMT and zSDMT improved in both POMS and AOMS, the improvement was significantly higher in POMS than in AOMS (+3.85±4.32 vs +1.76±2.80, p=0.010 for cSDMT, 0.41±0.40 vs 0.25±0.34, p=0.026 for zSDMT). After a re-baseline at month 6, 93% of POMS ( 27patients) and 85.3% of AOMS (29 patients, p=0.84) were NEDA-3. NEDA-3 condition, as well as any clinical and demographic parameter at baseline, did not explain SDMT improvement.The favorable outcomes observed in clinical, radiological, and neuropsychological parameters that we observed in our study support the consideration of natalizumab as a viable treatment option in POMS.